Chemical reprogramming for cell fate manipulation: Methods, applications, and perspectives - Wang, Jinlin; Sun, Shicheng; Deng, Hongkui (Cell stem cell, 2023)
Chemical reprogramming offers an unprecedented opportunity to control somatic cell fate and generate desired cell types including pluripotent stem cells for applications in biomedicine in a precise, flexible, and controllable manner. Recent success in the chemical reprogramming of human somatic cells by activating a regeneration-like program provides an alternative way of producing stem cells for clinical translation. Likewise, chemical manipulation enables the capture of multiple (stem) cell states, ranging from totipotency to the stabilization of somatic fates in vitro. Here, we review progress in using chemical approaches for cell fate manipulation in addition to future opportunities in this promising field.Chemical reprogramming offers an unprecedented opportunity to control somatic cell fate and generate desired cell types including pluripotent stem cells for applications in biomedicine in a precise, flexible, and controllable manner. Recent success in the chemical reprogramming of human somatic cells by activating a regeneration-like program provides an alternative way of producing stem cells for clinical translation. Likewise, chemical manipulation enables the capture of multiple (stem) cell states, ranging from totipotency to the stabilization of somatic fates in vitro. Here, we review progress in using chemical approaches for cell fate manipulation in addition to future opportunities in this promising field.